Porcine Breed, Sex, and Production Stage Influence the Levels of Health Status Biomarkers in Saliva Samples - Sánchez, Jorge; García, Ana; Ruiz, José María; Montes, Ana María; Cabezas-Herrera, Juan; Ros-Lara, Susana; De la Cruz, Ernesto; Gutiérrez, Ana María (Frontiers in Veterinary Science, 2019)
In this study, the influence of several factors such as breed, sex and production stage over the normal range values of salivary biomarkers of health status was evaluated in pigs. A total of 409 pigs of 2 different breeds (conventional Large White x Duroc and Iberian pigs) were included in the study. Animals were divided into different groups according to their sex (male or female) and the stage of the production cycle they were in (post-weaning, nursery, fattening and finishing). The levels of an inflammatory marker, adenosine deaminase (ADA), and two acute phase proteins, C-reactive protein (CRP) and haptoglobin (Hp) were measured in saliva samples. Moreover, the total antioxidant capacity level (TAC) was quantified for the first time in porcine saliva; therefore, an analytical validation and stability analysis during storage at -80ºC were also performed. Differences according to breed were observed for all the markers studied; thus, the influence of age and sex on the normal range values were studied separately for conventional and Iberian pigs. In Large White x Duroc pigs the overall median values of ADA, CRP, Hp and TAC were 282 U/L, 10.49 ng/mL, 0.88 µg/mL and 21.73 µM Trolox equivalents respectively. However, higher values of inflammatory marker and acute phase proteins were observed in males at the initial stages of the production cycle, while females presented higher values when they had reached sexual maturity. In Iberian pigs the overall median values observed were 585 U/L, 4.81 ng/mL, 0.63 µg/mL and 21.21 µM Trolox equivalents for ADA, CRP, Hp and TAC respectively with slight differences in the influence of the studied factors. Sex differences were not observed in the levels of acute phase proteins in Iberian pigs, probably due to the castration of males during the first days of life; however, ADA levels were found to be higher in male pigs at the end of the production cycle. It could be concluded that breed, sex and production stage influence the range values of salivary markers of health status in pigs and should be taken into account to further establish reference intervals.